Mycovirus-Induced Tenuazonic Acid Production in a Rice Blast Fungus Magnaporthe oryzae - Ninomiya, Akihiro; Urayama, Syun-ichi; Suo, Rei; Itoi, Shiro; Fuji, Shin-ichi; Moriyama, Hiromitsu; Hagiwara, Daisuke (Frontiers in Microbiology, 2020)
Fungi are a rich source of natural products with biological activities. In this study, we evaluated viral effects on secondary metabolism of the rice blast fungus Magnaporthe oryzae using an isolate of APU10-199A co-infected with three types of mycoviruses: a totivirus, a chrysovirus, and a partitivirus. Comparison of the secondary metabolite profile of APU10-199A with that of the strain lacking the totivirus and chrysovirus showed that a mycotoxin tenuazonic (TeA) acid was produced in a manner dependent on the mycoviruses. Virus reinfection experiments verified that TeA production was dependent on the totivirus. Quantitative reverse transcription PCR and RNA-sequencing analysis indicated the regulatory mechanism underlying viral induction of TeA: the totivirus activates the TeA synthetase gene TAS1 by upregulating the transcription of the gene encoding a Zn(II)2-Cys6-type transcription factor, TAS2. To our knowledge, this is the first report that confirmed mycovirus-associated regulation of secondary metabolism at a transcriptional level by viral reinfection. Because only treatment with dimethyl sulfoxide has been reported to trigger TeA production in this fungus without gene manipulation, our finding highlights the potential of mycoviruses as an epigenomic regulator of fungal secondary metabolism.